Formation and evolution of precipitates in high Cr ferritic heat-resistant steels. (May 2015) - Zhou, X. S.; Liu, Y. C.; Liu, C. X.; Yu, L. M.; Li, H. J.
<x content-type="archive" xml:space="preserve">Abstract</x> For high Cr ferritic heat-resistant steels, dispersion hardening has played a vital role in improving creep strength at high temperatures. In this paper, the various types of precipitates in high Cr ferritic steels are reviewed, concerning M3C, M23C6, MX, M2X, Laves phase and Z phase. The evolution of these precipitates is a complicated process, since the dissolution of one type of precipitate may be overlapped with the precipitation of another type or other types. The composition of some precipitations varies towards the equilibrium composition under certain conditions, which is relevant to the solubility and diffusivity of the alloying element, while the composition of some other precipitates changes slightly. For the precipitates in high Cr ferritic steels, the preferred nucleation sites involve prior austenite grain boundaries, lath boundaries, dislocations and the interfaces between the precipitates and the matrix.